Endearment Forms in Enlish and Uzbek Languages - Ortiqova Tursunoy Jumanazar kizi (Researchparks Publishing, 2022)
This article illustrates the expression of love in English and Uzbek with the help of various examples, examines the interrelationships, differences and differences between the words expressing love in English and Uzbek. The article also provides alternatives to the words dearment, which are used in both languages.